Induced Fit of C2H2 in a Flexible MOF Through Cooperative Action of Open Metal Sites. Issue 25 (9th May 2019) - Zeng, Heng; Xie, Mo; Huang, Yong‐Liang; Zhao, Yifang; Xie, Xiao‐Jing; Bai, Jian‐Ping; Wan, Meng‐Yan; Krishna, Rajamani; Lu, Weigang; Li, Dan
Abstract: Porous materials that can undergo pore‐structure adjustment to better accommodate specific molecules are ideal for separation and purification. Here, we report a stable microporous metal‐organic framework, JNU‐1, featuring one‐dimensional diamond‐shaped channels with a high density of open metal sites arranged on the surface for the cooperative binding of acetylene. Together with its framework flexibility and appropriate pore geometry, JNU‐1 exhibits an induced‐fit behavior for acetylene. The specific binding sites and continuous framework adaptation upon increased acetylene pressure are validated by molecular modeling and in situ X‐ray diffraction study. This unique induced‐fit behavior endows JNU‐1 with an unprecedented increase in the acetylene binding affinity (adsorption enthalpy: up to 47.6 kJ mol −1 at ca. 2.0 mmol g −1 loading). Abstract : Tailored pores : A flexible microporous metal‐organic framework (MOF) physisorbent, JNU‐1, exhibits an induced‐fit behavior for acetylene. This unique behavior endows JNU‐1 with an unprecedented increase in the acetylene binding affinity (adsorption enthalpy: up to 47.6 kJ mol −1 at ca. 2.0 mmol g −1 loading), which enables a remarkable selectivity towards acetylene over other gas molecules including carbon dioxide.